Analysis of Synonymous Codon Usage Patterns in Seven Different Citrus Species. (January 2013) - Xu, Chen; Dong, Jing; Tong, Chunfa; Gong, Xindong; Wen, Qiang; Zhuge, Qiang
We used large samples of expressed sequence tags to characterize the patterns of codon usage bias (CUB) in seven different Citrus species and to analyze their evolutionary effect on selection and base composition. We found that A- and T-ending codons are predominant in Citrus species. Next, we identified 21 codons for 18 different amino acids that were considered preferred codons in all seven species. We then performed correspondence analysis and constructed plots for the effective number of codons (ENCs) to analyze synonymous codon usage. Multiple regression analysis showed that gene expression in each species had a constant influence on the frequency of optional codons (FOP). Base composition differences between the proportions were large. Finally, positive selection was detected during the evolutionary process of the different Citrus species. Overall, our results suggest that codon usages were the result of positive selection. Codon usage variation among Citrus genes is influenced by translational selection, mutational bias, and gene length. CUB is strongly affected by selection pressure at the translational level, and gene length plays only a minor role. One possible explanation for this is that the selection-mediated codon bias is consistently strong in Citrus, which is one of the most widely cultivated fruit trees.